2019
DOI: 10.1038/s41467-019-10486-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of memory-like dendritic cell responses in vivo

Abstract: Dendritic cells (DCs), a vital component of the innate immune system, are considered to lack antigen specificity and be devoid of immunological memory. Strategies that can induce memory-like responses from innate cells can be utilized to elicit protective immunity in immune deficient persons. Here we utilize an experimental immunization strategy to modulate DC inflammatory and memory-like responses against an opportunistic fungal pathogen that causes significant disease in immunocompromised individuals. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 50 publications
0
103
0
Order By: Relevance
“…Recent work has shown that DCs can also show immune memory responses. In this regard, DCs isolated from mice exposed to the fungal pathogen Cryptococcus neoformans displayed strong interferon-γ (IFNγ) production and enhanced proinflammatory cytokine responses on subsequent challenge, which is indicative of a memory response 67 . These effects were dependent on epigenetic changes and were impaired by the treatment of mice with a histone methyltransferase inhibitor 67 .…”
Section: Diversity Of Cells That Can Develop Trained Immunitymentioning
confidence: 99%
“…Recent work has shown that DCs can also show immune memory responses. In this regard, DCs isolated from mice exposed to the fungal pathogen Cryptococcus neoformans displayed strong interferon-γ (IFNγ) production and enhanced proinflammatory cytokine responses on subsequent challenge, which is indicative of a memory response 67 . These effects were dependent on epigenetic changes and were impaired by the treatment of mice with a histone methyltransferase inhibitor 67 .…”
Section: Diversity Of Cells That Can Develop Trained Immunitymentioning
confidence: 99%
“…There is some evidence that DCs may also have memorylike capabilities. Studies using a vaccine strain of C. neoformans indicate that splenic DCs undergo histone modifications that enhance cytokine responses upon rechallenge with a virulent strain of C. neoformans (Hole et al, 2019). However, these DCs did not have a robust response to other secondary stimuli including LPS, S. aureus, and C. albicans.…”
Section: Trained Immunity: a Second Memory Bank For The Immune Systemmentioning
confidence: 99%
“…Additionally, training of DCs was recently reported. Murine DCs produced more cytokines in response to Cryptococcus neoformans and Staphylococcus aureus 70 days after pulmonary immunization with a recombinant C. neoformans strain expressing IFNγ, in contrast to naïve mice 45 . Two months, but not 2 weeks, after MVA prime and prior to MVA revaccination, we previously showed that blood monocytes, neutrophils, and cDCs were phenotypically "defense-ready".…”
Section: Discussionmentioning
confidence: 91%